N6-Methyladenosine regulator RBM15B acts as an independent prognostic biomarker and its clinical significance in uveal melanoma - Wang, Tianyu; Bai, Jianhao; Zhang, Yuanyuan; Xue, Yawen; Peng, Qing (Frontiers in Immunology, 2022)
Uveal melanoma (UM) is the most frequent intraocular malignant tumor in adults. N6-Methyladenosine (m6A) methylation is recognized as the most critical epigenetic change and is implicated in the development of many malignancies. However, its prognostic value in UM is poorly understood. RNA-seq and clinical data from The Cancer Genome Atlas (TCGA) help us better understand the relationship between m6A regulators and UM patients. Herein, four UM groups established by consensus clustering were shown to have different immune cell infiltrations and prognostic survival. Five m6A regulators, including RBM15B, IGF2BP1, IGF2BP2, YTHDF3, and YTHDF1, were associated with the prognosis of UM patients. Intriguingly, RBM15B was confirmed to be the only independent prognostic factor for UM and it was significantly correlated with clinicopathologic characteristics of UM. Notably, RBM15B expression was significantly negatively correlated with immune checkpoints. Furthermore, LINC00665/hsa-let-7b-5p/RBM15B axis and LINC00638/hsa-miR-103a-3p/RBM15B axis were found to be potential prognostic biomarkers in UM. In a nutshell, this work, through bioinformatics analysis, systematically described the gene signatures and prognostic values of m6A regulators. RBM15B is an independent protective prognostic factor, which may help us better understand the crosstalk within UM.